Bariatric Surgery Induces a Differential Effect on Plasma Aldosterone in Comparison to Dietary Advice Alone - Berney, Maxime; Vakilzadeh, Nima; Maillard, Marc; Faouzi, Mohamed; Grouzmann, Eric; Bonny, Olivier; Favre, Lucie; Wuerzner, Grégoire (Frontiers in Endocrinology, 2021)
Background and objectives The pathophysiological mechanisms linking weight loss to blood pressure (BP) reduction are not completely understood. The objective of this study was to compare the effect of weight loss after Roux-en-Y gastric bypass (RYGB) on BP, renin-angiotensin-aldosterone system (RAAS), and urinary electrolytes excretion to those of dietary advice. Methods This was a case-control prospective study including obese patients referred for RYGB (cases) and obese receiving diet advice only (controls). Ambulatory BP, plasma renin activity (PRA), plasma aldosterone concentration (PAC), and urinary electrolytes were measured before (M0) and after intervention (M3: 3 months and M12: 12 months). Results Twenty-five patients were included in the RYGB group and twelve patients in the control group. After 12 months, weight loss (-42 ± 11.5 vs -12.3 ± 6.3 kg in the control group, p=0.001) and decrease in PAC were more pronounced in the RYGB group (-34 ± 76 vs +14 ± 45 pg/ml in the control group, p=0.002). There was no difference in PRA between both groups (-0.08 ± 1.68 vs 0.01 ± 0.37 ng/ml/h, p=0.31). Sodium excretion was more marked in the RYGB group after 3 months only (-89 ± 14.9 vs -9.9 ± 27.9 mmol/day, p=0.009). The decrease in SBP was similar between both groups (-6.9 ± 9.9 vs -7.1 ± 11.9 mmHg in the controls, p=0.96). Conclusions Bariatric-induced weight loss induces a progressive decrease in PAC independently of PRA and sodium excretion. Whether this decrease in PAC affects target organ damage in the long term remains to be determined.